Pembuatan Aplikasi Pelayanan Rukun Tetangga di Kelurahan Pasar Lama - Ibrahim Ibrahim; Fitrah Yuridka; Ahmadi Ahmadi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The development of information technology is currently very pronounced and almost all fields have used it, access to information can be done anywhere and at any time, whether at home, work or even during holidays. Digital data management that can be done accurately, precisely and quickly. Utilization of digital information can be used as needed. In the service of residents in the Pasar Lama sub-district, data collection often occurs repeatedly, hardcopies are lost, data storage is not neatly arranged, there are new residents who are confused about how to move or come to that place. Includes population data collection, issuance of a letter of introduction or statement. The population service system in the Pasar Lama sub-district area is still bookkeeping or archiving so it is prone to redundancy in population data which can result in inaccurate population data, difficulties often occur when compiling monthly reports on population numbers, and there is still no population data archiving system resulting in data searches very difficult and prone to being lost. The aim of this service is to design an Information System to improve population services which is expected to make it easier for the Pasar Lama sub-district administrators to serve the population, thereby helping to achieve maximum work results and supporting fast and accurate information.